Amyloid Formation of Stefin B Protein Studied by Infrared Spectroscopy - Urban Novak; Eva Žerovnik; Ajda Taler-Verčič; MagdaTušek Žnidarič; Barbara Zupančič; Jože Grdadolnik (Frontiers in Bioscience-Landmark, 2023)
Background: Stefin B, an established model protein for studying the stability and mechanism of protein folding, was used for monitoring protein aggregation and formation of amyloid structure by infrared spectroscopy. Methods: The analyses of the integral intensities of the low frequency part of the Amide I band, which is directly connected to the appearance of the cross-β structure reveals the temperature but not pH dependence of stefin B structure. Results: We show that pH value has significant role in the monomer stability of stefin B. Protein is less stable in acidic environment and becomes more stable in neutral or basic conditions. While in the case of the Amide I band area analysis we apply only spectral regions characteristic for only part of the protein in cross-β structure, the temperature study using multivariate curve resolution (MCR) analysis contains also information about the protein conformation states which do not correspond to native protein nor protein in cross-β structure. Conclusions: These facts results in the slightly different shapes of fitted sigmoid functions fitted to the weighted amount of the second basic spectrum (sc2), which is the closed approximation of the protein spectra with cross-β structure. Nevertheless, the applied method detects the initial change of the protein structure. Upon the analysis of infrared data a model for stefin B aggregation is proposed.